The Impact of Company Growth, Size, Profitability, and Leverage on Tax Avoidance with Good Corporate Governance as a Moderating Variable - Rizky Fitriana Rosalin; Agnes Advensia Chrismastuti (SAFE-Network, 2023)
The research objective is to investigate the impact of Company Growth, Company Size, Profitability, and Leverage on Tax Avoidance with Good Corporate Governance as a moderating variable in Manufacturing Companies listed on the Indonesia Stock Exchange during the period 2017-2021. This study utilizes a quantitative method. The population and sample are obtained from the Indonesia Stock Exchange during the period 2017-2021. The research sample comprises 49 manufacturing companies listed on the Indonesia Stock Exchange during the period 2017-2021. Multiple linear regression analysis using the SPSS application is employed for data analysis. The results indicate that sales growth, company size, profitability, and leverage have a positive impact on tax avoidance, whereas good corporate governance weakens the influence of Company Growth, Company Size, Profitability, and Leverage on Tax Avoidance.